Sheet metal meso- and microforming and their industrial applications - Lai, Xin Min; Fu, Ming Wang; Peng, Lin Fa (Boca Raton, FL : CRC Press/Taylor & Francis Group, 2019)
The book presents a compilation of research on meso/microforming processes, and offers systematic and holistic knowledge for the physical realization of developed meso/microforming processes. It discusses practical applications in fabrication of meso/microscale metallic sheet-metal parts via sheet-metal meso/Microforming including industrial applications and examples--
OCLC-licensed vendor bibliographic record.
Keywords: Micromachining; Sheet-metal work; TECHNOLOGY & ENGINEERING / Technical & Manufacturing Industries & Trades